Not quite an academic, not quite professional services: supporting students’ wellbeing and development in the ‘third space’ as a peer-mentoring coordinator - Emma Norman (Journal of Learning Development in Higher Education)
Peer-to-peer support schemes, where more experienced students support other students, are a widely used tool in universities for supporting the student experience. Although their benefits for students are well researched, the extent of the work and pedagogical expertise required to coordinate peer schemes is not often acknowledged. This case study focuses on my experience of this and how my role in delivering personalised support to the students involved, developing and delivering teaching materials, and coordinating with staff puts me in the ‘third space’. In addition, I highlight some of the challenges in increasing recognition of this type of role in higher education and how I have addressed these in my context.